On the Computation of the Attenuation Constant by Using the Generalized Telegraphist’s Equations Based Electromagnetic Analysis Method - Simion, S. (Advanced Electromagnetics, 2023)
Numerical results for the attenuation constant obtained by using the generalized telegraphist’s equations (GTEs) based electromagnetic analysis method and comparison with the HFSS (High Frequency Structure Simulator) results are reported. To calculate the attenuation constant with the GTEs method, not only the amplitudes of the voltage modes but also the amplitudes of the current modes must be found. In this paper, it is demonstrated that the relationships reported by other authors for the amplitudes of the current modes are not correct and new ones are proposed. To validate these relationships, the attenuation constants for homogeneous and different partially dielectric-filled rectangular waveguides are computed for the fundamental propagation mode by using the GTEs based analysis method and the results are compared with those obtained with HFSS. It is shown that using the revised relationships for the amplitudes of the current modes, the GTE method can be used to compute accurately the propagation and attenuation constant, but only for propagation modes in which the components of the electric field are not oriented perpendicular to the interface between different dielectrics. This limitation is not due to the proposed current mode relationships, but is due to the GTE method which cannot highlight the electric field discontinuities.